REVIEW PAPER Neurological involvement in patients with rheumatic fever - Grzanka, Katarzyna; Pieczyrak, Robert; Kotulska, Anna; Kucharz, Eugeniusz Józef (Reumatologia/Rheumatology, 2005)
Sydenham’s chorea and pediatric autoimmune neuropsychiatric disorders associated with streptococcal infection (PANDAS) are clinical, neurological manifestations in rheumatic fever. Sydenham’s chorea is one of the diagnostic criteria of rheumatic fever. PANDAS is a group of neurological and psychiatric symptoms included: obsessive-compulsive disorders, tics and coexisting neurological signs. It is thought that all these manifestations have autoimmune pathogenesis.